Effects of Ginger supplementation on lipid profile: A systematic review and meta-analysis of randomized clinical trials - Zahra Fakhri *; Sakineh Shab-Bida; Safieh Firoozi; Kurosh Djafarian (Lorestan University of Medical Sciences, 2019)
Abstract Background: Some, but not all, experimental and clinical studies have suggested that ginger supplementation has beneficial effects on serum lipid profiles. Therefore, we conducted a meta-analysis to evaluate the ginger supplementation on human serum lipids. Methods: Systematic search for English published randomized controlled trials (RCTs) was performed up to April 2016 through electronic databases: Medline, EMBASE and Google Scholar. A total of seven RCTs were met inclusion criteria. The pooled weighted mean difference (MD) and its 95% confidence interval (CI) were calculated and pooled using using a random-effects model. Results: Ginger supplementation was associated with a significant reduction in mean serum total cholesterol (-13.31 mg/dL, 95% CI, -20.29 to -6.33 mg/dL, P=0.000), low-density lipoprotein cholesterol (-11.22 mg/dL; 95% CI, -18.37 to -4.06 mg/dL, p = 0.002), triglycerides ( -14.96 mg/dL; 95% CI, -22.13 to -7.79 mg/dL, p = 0.000); Increasing in high-density lipoprotein cholesterol level was not statistically significant (WMD = 0.12 mg/dL; 95% CI, -1.01 to 1.24 mg/dL, p =0.839. Conclusion: Ginger supplementation significantly improved lipid profile (LDL, TG and TC) and it may be an effective intervention for managing serum lipid status. Further, high-quality RCTs are required to identifying the ginger supplementation effects on HDL.